The Role of Expectation–Reality Discrepancy in Service Contracts. Issue 11 (21st July 2021) - Zhao, Xuying; Guo, Hong; Cai, Gangshu; Bandyopadhyay, Subhajyoti
Abstract : Service contracts are common practice in some industries while being eliminated in others. To investigate this phenomenon, we identify expectation–reality discrepancy (ERD) as a key determinant. A provider's ERD is defined as consumers' ex‐ante expected valuation minus their ex‐post realized valuation of the provider's service. Our analysis reveals that providers' contract strategies critically depend on their ERDs rather than the true service valuations. A provider with a higher ERD is more likely to enforce contracts, regardless of whether the true service valuation is higher than that of the competitor. Providers should enforce contracts only when they have positive ERDs. Furthermore, contracts have a competition‐intensifying effect: when providers enforce contracts, their competition on promoting consumer expectations through marketing efforts is intensified, leading to higher ERDs with contracts than without contracts. Finally, consumers and society as a whole may benefit from higher switching costs because positive ERDs may mislead consumers to make wrong switching decisions and switching costs can help deter such switching behaviors.